Tiempo de duración de aireación en el rendimiento en Lactuca sativa L. en un sistema hidropónico. Loreto, 2022 - Padilla Castro, Aaron Leonardo (2024)
This study aimed to evaluate the effect of aeration duration of the nutrient solution on the performance of Lactuca sativa L., using the floating root technique (FRT) in a hydroponic system in Loreto. Employing a Completely Randomized Design, four aeration treatments (3, 6, 9, and 12 minutes) were established, applied every 2 hours during the day, with 10 repetitions each. The results revealed that a 9-minute aeration is optimal, significantly improving plant growth and yield, reflected in increased plant height, root length, plant width, number of leaves, and an increase in leaf and total plant weight. Specifically, a significant difference (p<0.01) in total plant weight (106.80 g) with 9 minutes of aeration compared to 3 minutes of aeration (79.50 g) was highlighted, underscoring the importance of precise aeration time control. This finding emphasizes the relevance of adjusting the aeration time in hydroponic systems, especially in warm climate areas like Loreto, to optimize the performance of hydroponic crops such as lettuce, contributing to food security and the advancement of sustainable agricultural practices in tropical climate conditions.